Phase‐Controlled Synthesis of Nickel‐Iron Nitride Nanocrystals Armored with Amorphous N‐Doped Carbon Nanoparticles Nanocubes for Enhanced Overall Water Splitting. Issue 34 (31st July 2022) - Chen, Mingyu; Liu, Ying; Fan, Jiayao; Liu, Bingxue; Shi, Naien; Lin, Yue; Li, Xianzeng; Song, Wenqi; Xu, Dongdong; Xu, Xiangxing; Han, Min
Abstract: Transition metal nitrides (TMNs) nanostructures possess distinctive electronic, optical, and catalytic properties, showing great promise to apply in clean energy, optoelectronics, and catalysis fields. Nonetheless, phase‐regulation of NiFe‐bimetallic nitrides nanocrystals or nanohybrid architectures confronts challenges and their electrocatalytic overall water splitting (OWS) performances are underexplored. Herein, novel pure‐phase Ni2+ x Fe2− x N nanocrystals armored with amorphous N‐doped carbon (NC) nanoparticles nanocubes (NPNCs) are obtained by controllable nitridation of NiFe‐Prussian‐blue analogues derived oxides/NC NPNCs under Ar/NH3 atmosphere. Such Ni2+ x Fe2− x N/NC NPNCs possess mesoporous structures and show enhanced electrocatalytic activity in 1 m KOH electrolyte with the overpotential of 101 and 270 mV to attain 10 and 50 mA cm –2 current toward hydrogen and oxygen evolution reactions, outperforming their counterparts (mixed‐phase NiFe2 O4 /Ni3 FeN/NC and NiFe oxides/NC NPNCs). Remarkably, utilizing them as bifunctional catalysts, the assembled Ni2+ x Fe2− x N/NC||Ni2+ x Fe2− x N/NC electrolyzer only needs 1.51 V cell voltage for driving OWS to approach 10 mA cm –2 water‐splitting current, exceeding their counterparts and the‐state‐of‐art reported bifunctional catalysts‐based devices, and Pt/C||IrO2 couples. Additionally, the Ni2+ x Fe2− x N/NC||Ni2+ x Fe2− x N/NC manifests excellent durability for OWS. The findings presented here may spur the development of advanced TMNs nanostructures by combining phase, structure engineering, and hybridization strategies and stimulate their applications toward OWS or other clean energy fields. Abstract : Phase‐controlled synthesis of nickel‐iron nitride nanocrystals armored with amorphous N‐doped carbon (NC) nanoparticles nanocubes (NPNCs) is realized, which witnesses the phase‐dependent bifunctional electrocatalytic behaviors. To apply in overall water splitting, the pure‐phase Ni2+x Fe2− x N/NC NPNCs only needs 1.51 V to reach 10 mA cm −2 water‐splitting current, outperforming mixed‐phase NiFe2 O4 /Ni3 FeN/NC, NiFe oxides/NC, Pt/C/IrO2 couples, and most of reported bifunctional electrocatalysts.